Steering thermal photoassociation of magnesium atoms by two time-delayed femtosecond laser pulses - Zhang, Rong; Hu, Jin-Wei; Han, Yong-Chang; Fu, Bina; Shundalau, Maksim (Frontiers in Physics, 2023)
By solving the full-dimensional time-dependent Schrödinger equation with the thermal-random-phase wavepacket method, we investigate the photoassociation (PA) process of hot ($1000$ K) magnesium atoms induced by two time-delayed femtosecond laser pulses. Driven by the 840 nm femtosecond laser pulses, the Mg$_{2}$ molecules can be formed on the four excited states, $(1)^{1}Π_{g}$, $(1)^{1}Π_{u}$, $(2)^{1}Π_{u}$, and $(2)^{1}Σ^{+}_{u}$, from the initial electronic ground state $X^{1}Σ^{+}_{g}$. It is found that the three-photon couplings between $X^{1}Σ^{+}_{g}$ and the three ungerade states ($(1)^{1}Π_{u}$, $(2)^{1}Π_{u}$, and $(2)^{1}Σ^{+}_{u}$) play dominant roles in the population transfer process. By scanning the pulse duration $τ$ from 50 to 200 fs, and varying the delay time $δ t_{0}$ from 0 to $2 τ$ fs, we find that the final PA population is strongly dependent on the two parameters. For a given $δ t_{0}$, the parameter $τ$ can induce a significant variation ($2\sim6.8$ times) for the final PA population transfer, and for a given $τ$, one can also obtain a significant variation ($2.7\sim3.5$ times) of the final PA population by varying $δ t_{0}$. Additionally, the dynamics of the coherently vibrational wavepackets of the four excited states are also influenced by the two parameters.